Türkiye ve İtalya'da bölgesel gelişmişlik farklarının giderilmesinde Avrupa Birliği bölgesel politikasının etkinliği - Selçuk, Yeliz (My University, 2019)
Çalışmanın inceleme alanını oluşturan bölgesel gelişmişlik farklılıkları her ülkenin yaşadığı sorunlardandır. Sorun, ülkelerin dünyadaki önemli siyasi ve ekonomik kuruluşlardan olan Avrupa Birliği’ne uyum sürecinde entegrasyonlarını yavaşlatıcı etki yapmaktadır. Ancak, 1957 yılında 6 ülke ile kurulan Birlik, uyguladığı bölgesel politika sayesinde ekonomik eşitsizliklerin azaltılmasında önemli adımlar atmıştır. Ülke içinde bölgeler arasındaki farklılıklar, birliğin merkez kurucu ülkelerinden İtalya ve aday ülke Türkiye’nin de mücadele ettiği problemlerdendir. Ekonomik eşitsizlikler sorunu, her ülke için aynı olmasına rağmen, yönlerinde farklılıklar görülmektedir. İtalya’da Kuzey-Güney arasında yaşanan sorun, Türkiye’de Doğu-Batı yönünde seyir etmektedir. Bu durum, politikaların gelişim seyrini ve düzeyini etkilemektedir. Ülkeler, AB’ye uyum sürecinde farklılıkları sonlandırmak amacıyla bölgesel kalkınma ajanslarının kurulumunu desteklemişlerdir. Bu çalışmanın temel bulgusu olarak Avrupa Birliği içerisinde yer alan Bölgesel Kalkınma Ajansları’nın hem Türkiye hem de İtalya içerisinde bölgesel gelişmişlik farklarının giderilmesinde etkili bir araç olduğu ortaya konmuştur.

The regional development differencies that constitute the study area of the thesis are the problems experienced by each country. The problem creates a slowing effect in the integration of countries in the process of integration with the European Union which is one of the most important political and economic insttutions in the World. However, the Union, established in 1957 with 6 countries, has taken important steps in reducing economic inequalities thanks to the regional policy it has implemented. The differencies between the regions in the country, are the problems struggled, one of the founding countries of the Union as Italy and a candidate country as Turkey. Although the problem of economic inequalities is the same for each country, there are differences in their aspects. Problems between North-South in Italy, in Turkey is looking East-West direction. This situation affects the progress and level of the policies. The countries have supported the establishment of regional development agencies in order to end differences in the EU harmonization process. The establishment of RDAs both in Turkey and Italy is one of the effective tools in reducing the problem. Further, it can be claimed as the main outcome of this study that theare RDA’s beneficial for easing the regional development differences both in Italy and Turkey.
Keywords: Avrupa Birliği; Bölgesel eşitsizlikler; Bölgesel Gelişmişlik Farklılıkları; Bölgesel Kalkınma; Bölgesel Kalkınma Ajansları; Cohesion Policy; European Union; Italy; İtalya; Regional Development; Regional Development Agencies; Regional Development Differencies; Regional disparities; Turkey; Türkiye; Uyum Politikası